2021
DOI: 10.1038/s41598-021-81183-x
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, optimization and characterization of allantoin-loaded chitosan nanoparticles to alleviate ethanol-induced gastric ulcer: in-vitro and in-vivo studies

Abstract: Allantoin (ALL) is a phytochemical possessing an impressive array of biological activities. Nonetheless, developing a nanostructured delivery system targeted to augment the gastric antiulcerogenic activity of ALL has not been so far investigated. Consequently, in this survey, ALL-loaded chitosan/sodium tripolyphosphate nanoparticles (ALL-loaded CS/STPP NPs) were prepared by ionotropic gelation technique and thoroughly characterized. A full 24 factorial design was adopted using four independently controlled par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 82 publications
(123 reference statements)
1
21
0
Order By: Relevance
“…The IC 50 values for CCNPs and CNPs were 14, 20, and 155.6 µg/mL and 394, 285, and 311 µg/mL in A549, PANC-1, and normal broblast cells, respectively, which agreed with results from previous studies (40,41). These results indicated that CCNPs could improve the e ciency of chrysin on cell growth inhibition (40).…”
Section: Discussionsupporting
confidence: 88%
“…The IC 50 values for CCNPs and CNPs were 14, 20, and 155.6 µg/mL and 394, 285, and 311 µg/mL in A549, PANC-1, and normal broblast cells, respectively, which agreed with results from previous studies (40,41). These results indicated that CCNPs could improve the e ciency of chrysin on cell growth inhibition (40).…”
Section: Discussionsupporting
confidence: 88%
“…Ethanol is used for inducing experimental gastric ulcers in rats either alone [ 19 , 20 ] or in combination with hydrochloric acid (HCL) [ 21 , 22 ]. Ethanol was used for the induction of gastric ulcers as we observed it to be highly effective in producing gastric ulcers in fasted rats [ 7 ], the ulceration was observed in all the animals administered ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…For polymers with enhanced hydrophilicity, the diffusion coefficient is low [ 50 ]. The decrease in diffusion coefficient has been explained byenhanced cluster size of the diffuse species, which become less movable [ 51 ].…”
Section: Resultsmentioning
confidence: 99%